WGS identifies Lynch syndrome (LS) patients and uncovers a large family with MSH2-related LS in Southern Thailand - Worrawit Wanitsuwan; Kanet Kanjanapradit; Supakool Jearanai; Yuthasak Suphasynth; Pongsatorn Supaattagorn; Sukanya Vijasika; Surasak Wanram; Chumpol Ngamphiw; Vorthunju Nakhonsri; Sissades Tongsima; Palakorn Satsue; Natnaree Sangkeaw; et al. (PLoS ONE, 2026)
This study aimed to investigate Lynch Syndrome (LS)-related germline variants among Southern Thai patients with colorectal cancer (CRC) and other LS-associated cancers who met the revised Bethesda guidelines. A total of 132 probands suspected of LS underwent whole genome sequencing (WGS). Eleven germline variants including pathogenic variants (PVs), likely pathogenic variants (LPVs), and potential variants of uncertain significance (VUSs) in DNA mismatch repair (MMR) genes were identified in twenty-six individuals (20%). Among these, six PVs/LPVs/VUSs were detected in MLH1 , three in MSH2 , and two in PMS2 . Notably, the MSH2 c.1237C > T PV was detected in ten probands who were determined to share a common ancestry. Subsequent targeted sequencing of 56 relatives revealed fifteen additional carriers, four had already developed CRC or ampullary cancer, while colonoscopy surveillance detected polyps in two others. The benefit-cost ratio (BCR) analysis demonstrated the greater cost-effectiveness of genetic testing compared to endoscopic surveillance to all relatives at risk. Although our cohort is clinically enriched and does not reflect the population prevalence of LS in Southern Thailand, these findings highlight the substantial LS burden within high-risk families and underscore the importance of incorporating genetic screening, counseling, and tailored surveillance strategies into clinical practice.